2014
DOI: 10.1007/s00216-014-7680-4
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinium ionic liquid-modified silica as a novel stationary phase for high-performance liquid chromatography

Abstract: A novel stationary phase based on quinolinium ionic liquid-modified silica was prepared and evaluated for high-performance liquid chromatography. The stationary phase was investigated via normal-phase (NP), reversed-phase (RP), and anion-exchange (AE) chromatographic modes, respectively. Polycyclic aromatic hydrocarbons, phthalates, parabens, phenols, anilines, and inorganic anions were used as model analytes in chromatographic separation. Using the newly established column, organic compounds were separated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Since the original studies [10, 14, 22], researchers have reported retention behavior for a very limited number of PAHs (especially isomers) with the following polar functionalized stationary phases: NH 2 [15, 29], triamine [30, 31], silica [30], alumina [30], 2,4-dinitroanilinooctaylsilica [31], 2,3,6-trinitroanillinooctylsilica [31], aminocyano [15, 32], dihydroxypropyl propyl ether [33], nitrophenyl [32], poly(4-vinylpyridine)-grafted silica [34], 3-(2,4-Dinitroanilino)propyl [30, 31, 35], and hypercrosslinked polystyrene [35]. Despite these additional polar stationary phases, the NH 2 phase has been the predominant phase used for NPLC to isolate isomeric PAHs based on the number of aromatic carbon atoms [6, 7, 9].…”
Section: Resultsmentioning
confidence: 99%
“…Since the original studies [10, 14, 22], researchers have reported retention behavior for a very limited number of PAHs (especially isomers) with the following polar functionalized stationary phases: NH 2 [15, 29], triamine [30, 31], silica [30], alumina [30], 2,4-dinitroanilinooctaylsilica [31], 2,3,6-trinitroanillinooctylsilica [31], aminocyano [15, 32], dihydroxypropyl propyl ether [33], nitrophenyl [32], poly(4-vinylpyridine)-grafted silica [34], 3-(2,4-Dinitroanilino)propyl [30, 31, 35], and hypercrosslinked polystyrene [35]. Despite these additional polar stationary phases, the NH 2 phase has been the predominant phase used for NPLC to isolate isomeric PAHs based on the number of aromatic carbon atoms [6, 7, 9].…”
Section: Resultsmentioning
confidence: 99%
“…Pyridinium-modified phases could also be synthesized from larger pyridine derivatives, such as 4,4 0 -dipyridine [72] and quinoline [73]. Dipyridinium-modified silica (Sil-C 3 DiPy-Cl) could be used for IE separation of organic anions and RP separation of polycyclic aromatic hydrocarbons (PAHs) and phenols.…”
Section: Normal-phase Modementioning
confidence: 99%
“…Melamine can deceptively make higher content of nitrogen in the food, especially in the powder infant formula. This substance can be accumulated in infants for long time, causing severe renal failure, even death [40]. Detection of melamine is of practical significance.…”
Section: Chromatographic Applicationmentioning
confidence: 99%